Spermidine treatment limits the development of the fungus in flax shoots by suppressing polyamine metabolism and balanced defence reactions, thus increasing flax resistance to fusariosis - Augustyniak, Beata; Wojtasik, Wioleta; Sawuła, Agnieszka; Burgberger, Marta; Kulma, Anna (Frontiers in Plant Science, 2025)
IntroductionFlax (Linum usitatissimum) is an important industrial crop in temperate regions, but fungal diseases, especially those caused by Fusarium oxysporum sp. lini, pose a serious risk. These infections can lead to major crop losses, reducing interest in flax cultivation.MethodsThis study investigated the effects of exogenous spermidine (Spd) on the interactions between flax and Fusarium oxysporum sp. lini. Flax plants treated with either 10 mM or 100 mM Spd were monitored for changes in polyamine levels, gene expression, and hydrogen peroxide (H2O2) content following infection.Results and discussionNotably, plants treated with 10 mM Spd showed enhanced resistance, exhibiting better phenotypic health and lower fungal murein levels, especially in shoots. Chitinase expression in these plants remained similar to or lower than control levels, suggesting minimal additional defence activation was required. Additionally, a marked ROS burst occurred two days post-infection, followed by redox balance restoration, indicating a controlled defence response. These results suggest that moderate Spd treatment improves flax resilience against fusarium wilt while avoiding excessive defence activation, highlighting Spd’s potential for sustainable crop protection strategies.